Effects of Species Diversity on the Aboveground Biomass of Acacia mangium in a Mixed-Species Forest Stand in Thach That, Hanoi - Thi Nhat Minh, Doan; Thu Hang, Nguyen; Hung Cuong, Nguyen; Van Manh, VU (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2S, 2025)
Mixed-species plantations are considered as a pathway to sustainable forest management due to potential gains in productivity and ecosystem services compared with monocultures. Evidence on the relationship between species diversity and biomass in tropical plantations - particularly for crops such as Acacia mangium ( A. mangium ) - remains limited. This study tests the hypothesis that aboveground biomass (AGB) of A. mangium increases with forest species diversity. Data were collected in a 1-ha Marteloscope plot in Thach That (Hanoi), comprising 916 trees from 14 species. AGB was estimated using species-specific allometric equations; species diversity was characterized using the Shannon, Simpson, Berger–Parker, and evenness indices. Regression analyses employed three model forms (additive, exponential, and multiplicative) and were evaluated with AIC, BIC, R², and MSE. The exponential model provided the best representation of the relationships among variables. Notably, the effects of species diversity on biomass were nonlinear and heterogeneous, depending on model specification, some diversity indices tended to show negative associations with individual-tree biomass. The study underscores the importance of model-form selection when analyzing the diversity–biomass relationships and suggests expanding the Marteloscope network and integrating remote-sensing data to enable upscaling and to support evidence-based management of mixed-species plantations.